Participación de los jóvenes en la gestión municipal de la provincia de Trujillo, año 2016 - Valderrama Escobar, Víctor Alfredo (2017)
ABSTRACT The research focuses on the participation of young people in the management of the Provin-cial Municipality of Trujillo, from different aspects and fields of intervention, such as: youth organizations (representativeness - empowerment) and work regime (young people with ac-cess to work , As civil servants, professional services and promoters). The central purpose is the impact of youth participation based on the results obtained, after the opportunity to pro-pose, execute and evaluate their activities (youth organizations) and functions (municipal workers). The approach to the problem arises from the professional, organizational and par- ticipative performance of young people in municipal management; Their involvement and empowerment in the occupied spaces (through the municipal units); Always considering the access door to the position assumed, under labor, organizational and participatory commit-ments. To develop the work, it was necessary to follow a participatory methodology; Ethnographic work, observation, life histories, and the application of a survey to analyze the assessment of young people on the role they play from the opportunity offered by the Provincial Municipali-ty of Trujillo. The results allowed us to analyze the socio-cultural reality of the informants, as well as the activities they perform based on their work and common and particular interests in the district of Trujillo. The entry to the political and social groups that are presented as the opportunity to access a job that allows them to develop personally and professionally. Young people need opportunities to participate in different fields, but they also need more professional training according to the positions they hold to play an efficient role. The chal-lenges presented by this globalized world make competitiveness a personal and institutional challenge.